2021
DOI: 10.1021/acsami.1c01441
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation Dynamics in Sulfate-Loaded Lanthanide Triphosphonates. Proton Conductivity and Application as Fillers in PEMFCs

Abstract: Phase transformation dynamics and proton conduction properties are reported for cationic layer-featured coordination polymers derived from the combination of lanthanide ions (Ln 3+ ) with nitrilo-tris(methylenephosphonic acid) (H 6 NMP) in the presence of sulfate ions. Two families of materials are isolated and structurally characterized, i.e., [Ln 2 (H 4 NMP) 2 (H 2 O) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Metal–organic frameworks (MOFs) based on coordination chemistry with more porous structures are featured by designability, making the structures and functions integrated into an extreme periodic lattice matrix at an atomic-level scale and providing more space for material design. , Both inorganic building units and organic ligands can be tailored by choosing proper metal ions and organic groups to create novel compounds for various applications, such as sensors, proton conductors, , molecular separation, or heterogeneous catalysts. , Uranium-based MOFs (UMOFs) stand out among many actinides as the most studied ones due to their excellent optical properties. , As one of the essential elements for nuclear science and technology, uranium plays a crucial role in the nuclear fuel cycle process. Therefore, understanding uranium’s physical and chemical properties are fundamental to reducing radioactive waste and raising the level of the chemical process to make nuclear energy safer, more efficient, and sustainable .…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) based on coordination chemistry with more porous structures are featured by designability, making the structures and functions integrated into an extreme periodic lattice matrix at an atomic-level scale and providing more space for material design. , Both inorganic building units and organic ligands can be tailored by choosing proper metal ions and organic groups to create novel compounds for various applications, such as sensors, proton conductors, , molecular separation, or heterogeneous catalysts. , Uranium-based MOFs (UMOFs) stand out among many actinides as the most studied ones due to their excellent optical properties. , As one of the essential elements for nuclear science and technology, uranium plays a crucial role in the nuclear fuel cycle process. Therefore, understanding uranium’s physical and chemical properties are fundamental to reducing radioactive waste and raising the level of the chemical process to make nuclear energy safer, more efficient, and sustainable .…”
Section: Introductionmentioning
confidence: 99%
“…Porous coordination polymers (PCPs) , and metal–organic frameworks (MOFs) comprising metal ions and hydrogen-bonded organic frameworks (HOFs) , received extreme attention as solid-state proton conductors and achieved excellent progress. However, because their synthesis process is relatively complex with tough conditions, the low yield is still limiting its large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…Despite rapid economic development and improving quality of life, the environmental problems we rely on for survival are also suffering the most severe test. The energy problems have also become our urgent demand. A proton-exchange membrane fuel cell (PEMFC) is an unclouded and pollution-free energy source that has attracted extensive attention due to its characteristics of low noise, fast start-up, easy integration, environmental protection, and green. A Nafion membrane, as a kind of proton-exchange membrane (PEM), has become the most commonly used choice because of its good chemical stability, high mechanical strength, and good proton conductivity. However, a Nafion membrane also has a major disadvantage; that is, under high-temperature and low-humidity conditions, there will be a serious water loss and proton conductivity decline phenomenon. In order to improve the conductivity of the Nafion membrane, it has been reported that crystalline materials are doped into Nafion solution. ,, …”
Section: Introductionmentioning
confidence: 99%